Spontaneous Return of Biodiversity in Restored Subtropical Thicket: Portulacaria afra as an Ecosystem Engineer. Issue 6 (25th February 2013) - van der Vyver, Marius L.; Cowling, Richard M.; Mills, Anthony J.; Difford, Mark
Abstract An accepted criterion for measuring the success of ecosystem restoration is the return of biodiversity relative to intact reference ecosystems. The emerging global carbon economy has made landscape‐scale restoration of severely degraded Portulacaria afra (spekboom)‐dominated subtropical thicket, by planting multiple rows of spekboom truncheons, a viable land‐use option. Although large amounts of carbon are sequestered when planting a monoculture of spekboom, it is unknown whether this is associated with the return of other thicket biodiversity components. We used available carbon stock data from degraded, restored, and intact stands at one site, and sampled carbon stocks at restored stands at another site in the same plant community. We also sampled plant community composition at both sites. The total carbon stock of the oldest (50 years) post‐restoration stand (250.8 ± 14 t C ha−1) approximated that of intact stands (245 t C ha−1) and we observed a general increase in carbon content with restoration age (71.4 ± 24 t C ha−1 after 35 and 167.9 ± 20 t C ha−1 after 50 years). A multiple correspondence analysis separated degraded stands from stands under restoration based on ground cover, floristic composition, and total carbon stock. Older post‐restoration and intact stands were clustered according to woody canopy recruit abundance. Our results suggest that spekboom is an ecosystem engineer that promotes spontaneous return of canopy species and other components of thicket biodiversity. The spekboom canopy creates a cooler micro‐climate and a dense litter layer, both likely to favor the recruitment of other canopy species.